2018
DOI: 10.1111/dth.12566
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in children with moderate to severe psoriasis treated with TNF inhibitors in comparison to conventional agents

Abstract: Association of childhood psoriasis with metabolic syndrome has not been studied well. TNF-alfa contributes to the inflammation seen in metabolic syndrome, and recently etanercept has shown to reduce the levels of inflammatory markers. Assessment of prevalence of metabolic syndrome in juvenile psoriasis patients in Kuwait. We included 236 patients with moderate to severe psoriasis below 18 years treated for at least 24 weeks with TNF inhibitors (Group A), and equal number of age and sex matched cases treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
1
0
1
Order By: Relevance
“…Six months of anti-TNF-α treatment showed lesser association with MBS. Fasting blood glucose and serum TG were also significantly lower in a number of patients in this group [40]. These data clearly suggested that the anti-TNF-α treatment is not only beneficial for the treatment of the skin lesions of psoriasis but also has a positive effect on MBS.…”
Section: Expert Opinionsupporting
confidence: 53%
See 1 more Smart Citation
“…Six months of anti-TNF-α treatment showed lesser association with MBS. Fasting blood glucose and serum TG were also significantly lower in a number of patients in this group [40]. These data clearly suggested that the anti-TNF-α treatment is not only beneficial for the treatment of the skin lesions of psoriasis but also has a positive effect on MBS.…”
Section: Expert Opinionsupporting
confidence: 53%
“…Ixekizumab provided sustained treatment responses with a PASI 75 and sPGA 0/1 of 90% and 81% at 48 weeks, respectively. In terms of safety, 56% of the patients treated with ixekizumab reported AEs against 45% of the patients in the placebo group [40]. Ixekizumab was recently FDA-approved for the treatment of plaque type psoriasis in children ≥6 years of age.…”
Section: Ixekizumabmentioning
confidence: 99%
“…По данным ряда авторов, ранние метаболические нарушения, изменение состава и функций липидов связаны с системным воспалением при псориазе [31]. По результатам одного крупного ретроспективного исследования, терапия ингибиторами TNF ␣ уменьшает распространенность метаболического синдрома у детей с псориазом, что также свидетельствует в пользу концепции о роли системного воспаления в развитии метаболического синдрома [32]. Сдвиг липидного профиля в сторону преобладания атерогенных фракций липидов повышает риск развития сердечно-сосудистых заболеваний у детей с псориазом ввиду нарушения процессов экстракции макрофагами липидов из сосудистой стенки [31,33].…”
Section: метаболический синдром дислипидемия и инсулинорезистентностьunclassified